Quantifying societal burden of radiation-induced small bowel toxicity in patients with rectal cancer - Kimpe, Eva; Parmentier, Riet; Busschaert, Sara-Lise; De Mey, Johan; Barbé, Kurt; De Ridder, Mark; Putman, Koen (Frontiers in Oncology, 2024)
In the era of rapid succession of innovations in oncology care, the focus has shifted to selecting treatments that provide the best long-term quality of life for patients at a reasonable societal cost. Research demonstrated that the cost of capital investment is the main barrier to the broad implementation of advanced radiotherapy techniques. Our analyses demonstrated the large potential long-term cost-saving and improved quality of life of more advanced radiotherapy techniques. Such cost-effectiveness analyses have become an integral component of health technology assessments and therefore have an impact on reimbursement decisions and investments in novel cancer treatments. Hence, a more complete inclusion of benefits and costs in cost-effectiveness analyses is crucial to assess innovation in cancer care.